SECTORS PRODUCING AGRICULTURAL PRODUCTS AND THEIR STATISTICAL ANALYSIS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Currently, there are three types of producers in the market of agricultural products: q agricultural enterprises, dehkan (personal assistant) farms and farms (Fig. 1.1). If the first two of these are operating in a traditional way, the last one is a relatively "new" production sector that started its activity after the Republic of Uzbekistan gained independence.